Pengaruh Scientific Approach Melalui Aplikasi Zoom Meeting terhadap Keaktifan Belajar Siswa - Suswandari, Meidawati (Program Studi Pendidikan Bahasa dan Sastra Indonesia FKIP Universitas Islam Riau, 2021)
This study aims to determine the effect of the scientific approach through the zoom meeting application on the learning activeness of students at Palur 3 Elementary School. The research method uses quantitative research. The research design used a pre post test from the control class and the experimental class. The independent variable in this study is a scientific approach through the zoom meeting application. The dependent variable in this study is student learning activeness. The research was conducted in grade V of the 3 Palur Elementary School. The data collection tool used was a questionnaire. The data analysis technique uses the analysis prerequisite test which includes the normality test and the homogeneity test which is then followed by the hypothesis test (t-test) using SPSS. The results showed that the scientific approach through the Zoom meeting media influenced the learning activeness of the fifth grade students of SD Negeri 3 Palur. This can be seen from the results of the analysis test using the Paired Sample Test, the tcount was 9,143 with Sig 2 tailed of 0,000 with a t-table value of 2.101, indicating that tcount> ttable was 9.143> 2.101.